Diving patterns in the Antarctic Shag - Casaux, Ricardo Jorge (2004)
The diving patterns of the Antarctic Shag ( Phalacrocorax bransfieldensis ) were studied by direct observation on individuals foraging at Harmony Cove, Nelson Island, South Shetland Islands, during the 1995/96 and 1996/97 breeding seasons. The individuals observed foraged in shallow waters, mainly solitarily and presumably dived aerobically. The shags displayed relatively short diving bouts composed of few dives. During the 1995/96 breeding season, the duration of the dives decreased with the increase in the number of dives per bout and increased with the diving depth. These relationships were not statistically significant in 1996/97. In both seasons, the duration of the dives was positively related with both the surface resting time preceding and succeeding the dive, which may indicate that these birds display anticipatory or reactive dives probably according to the foraging conditions. Shags at the surface were seen swallowing fish longer than 15 cm; smaller fish as well as invertebrates may have been ingested underwater. The mean diving efficiencies of the bouts fall within the range reported for phalacrocoracids, but values of diving efficiency below unity were observed.